2016
DOI: 10.1080/2162402x.2016.1216290
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of stage III/IV melanoma patients with long NY-ESO-1 peptide and CpG-B elicits robust CD8+ and CD4+ T-cell responses with multiple specificities including a novel DR7-restricted epitope

Abstract: Long synthetic peptides and CpG-containing oligodeoxynucleotides are promising components for cancer vaccines. In this phase I trial, 19 patients received a mean of 8 (range 1-12) monthly vaccines s.c. composed of the long synthetic NY-ESO-1 79-108 peptide and CpG-B (PF-3512676), emulsified in Montanide ISA-51. In 18/18 evaluable patients, vaccination induced antigen-specific CD8C and CD4 C T-cell and antibody responses, starting early after initiation of immunotherapy and lasting at least one year. The Tcells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Several clinical trials have been conducted investigating vaccines and cellular therapies targeting these shared tumor antigens. In one such trial, melanoma patients immunized with NY‐ESO‐1 peptides and CpG adjuvant mounted CD8 + and CD4 + T cell responses 26 . Despite apparent antigen‐specific T cell responses, clinical efficacy has been limited in patients with established tumors receiving these and similar vaccines.…”
Section: Which Antigens Do T Cells Recognize In Cancer?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical trials have been conducted investigating vaccines and cellular therapies targeting these shared tumor antigens. In one such trial, melanoma patients immunized with NY‐ESO‐1 peptides and CpG adjuvant mounted CD8 + and CD4 + T cell responses 26 . Despite apparent antigen‐specific T cell responses, clinical efficacy has been limited in patients with established tumors receiving these and similar vaccines.…”
Section: Which Antigens Do T Cells Recognize In Cancer?mentioning
confidence: 99%
“…In one such trial, melanoma patients immunized with NY-ESO-1 peptides and CpG adjuvant mounted CD8 + and CD4 + T cell responses. 26 Despite apparent antigen-specific T cell responses, clinical efficacy has been limited in patients with established tumors receiving these and similar vaccines. This lack of efficacy may be due to either the immunosuppressive tumor microenvironment or an inherent defect in the T cell repertoire recognizing these antigens.…”
Section: Which Antigens Do T Cells Recognize In Cancer?mentioning
confidence: 99%
“…Given the precursor frequencies of antigen-specific T cells in peripheral blood samples, a conventional highly sensitive assay was used to quantify antigen-specific T-cell responses. [32][33][34] Thawed PBMCs rested for 5 hours in RPMI (Invitrogen), and 8% human AB serum (HS; Biowest) supplemented with penicillin or streptomycin and betamercaptoethanol at 37 C (2.1) were plated in 96-well plates at 10E5 cells per well in RPMI-8% human serum. Peptide pools (see the following list) were added in replicates (2-6 wells per condition).…”
Section: In Vitro Stimulation Of Antigen-specific T Cellsmentioning
confidence: 99%
“…Instead, these antibodies facilitate the formation of immune complexes, with NY-ESO-1 protein, for effective cross presentation by dendritic cells [44]. It is well understood that, in NY-ESO-1 expressing tumors, key anti-tumor responses involve integrated antibody, CD4 + and CD8 + T cell responses leading to robust immune response with significant clinical benefit [49][50][51][52]. Interestingly, clinical trials have shown that, therapeutic interventions against NY-ESO-1(for e.g.…”
Section: Immunogenicity Of Ny-eso-1 Ny-eso-1 Humoral Responsesmentioning
confidence: 99%